(untitled) - Ferguson, Arron (Boston, Mass., 2007)
In today's fast-paced, information-packed world, it's critical for businesses to organize and manipulate the data gathered from customers, sales, and product responses, etc. into usable information. Content Management Systems (CMS) can do this for your business easily and efficiently. There are several commercial systems available, but customizing one for your specific needs is usually necessary based on your data. Creating Content Management Systems in Java teaches you how to develop an open source CMS from scratch using XML as the storage mechanism, XSLT as the presentation layer, and Java and JSPs & Servlets to realize the multi-tiered architecture. The book also covers data modeling in XML and the use of XSLT as a presentation vehicle for custom XML formats. Creating Content Management Systems in Java is written for Web and software developers (specifically Java developers) who wish to learn more about the field of content management. The book provides a practical, applied perspective with complete demonstrations using code to show you how a solution or feature can be implemented. Throughout the book you will work through the development of a complete, open source, working CMS example, beginning with the conceptual ideas of content management. From there you'll dive into the exploration of practical design solutions, and then move into the final implementations in each tier of the software that becomes the CMS. To benefit the most from this book, you should already know the Java programming language and have a basic understanding of the Web. You do not need to know XML, XSLT, CSS, or XHTML because these topics are covered thoroughly, although a basic understanding will be helpful. So, if you need to learn more about CMS development, this is the book for you.
Keywords: Digital media,Multimedia systems,Java (Computer program language),Truyền thông kỹ thuật số,Quản trỉ hệ thống truyền thông; Management,Management,Quản trị